Assessment of Association between Thyroid Disorders and Gout (Academia Journal of Medicine, 2020)
Background: Thyroid hormones (THs) play their parts in multiple events, including development, growth, metabolism, and reproduction. Recently, attentions have been paid to THs again due to the increasing prevalence of metabolic diseases, because THs boost the body energy metabolism. Hence; the present study was conducted for assessing association between thyroid disorders and gout. Subjects and Methods: A total of 50 subjects were enrolled. Complete demographic details of all the subjects were obtained. Out of 50 subjects, 25 subjects were of subclinical hypothyroidism while the remaining 25 subjects were healthy control. Complete demographic details of all the subjects were obtained. The thyroid-stimulating hormone (TSH) test was conducted in all the patients. Triiodothyronine (T3) and thyroxine (T4) hormonal tests were also carried out. The diagnosis of subclinical hypothyroidism was performed by the physician by interpreting the results of tests based on increased TSH levels based on the age and normal range of T3 and T4. Serum uric acid levels were obtained from all the patients and the results were subjected to statistical analysis. All the results were obtained and analysed by SPSS software. Results: Mean TSH levels of the subjects of the study group and control group was 9.2 mIU/L and 4.5 mIU/L. Significant results were obtained while comparing the mean TSH levels among the subjects of the study groups. However; non-significant results were obtained while comparing the mean uric acid levels among the patients of the study group and control group. Conclusion: From the above results, authors conclude that no significant correlation exist between thyroid disorders and gout.
Keywords: Thyroid; Gout